Penerapan virtual laboratorium di masa pandemi covid-19 untuk meningkatkan keterampilan proses sains mahasiswa calon guru fisika - Hamdani Hamdani; Erwina Oktavianty (IKIP PGRI Pontianak, 2022)
The implementation of virtual labs during the pandemic is carried out to improve science process skills. Any 32 physics teacher candidates were involved in this study to take the pretest, posttest, and learning using a virtual lab. The results showed that there was an increase in the science process skills of prospective physics teacher by 0.51 in the medium category. The ability to interpret (0.62), design experiments (0.59), hypothesize (0.47), observe (0.58), predict (0.36) and classify (0.57) experienced an increase in the moderate category. The increase in the high category occurred in the aspect of applying the concept (0.79). Virtual labs can be used as an alternative to online or offline learning to improve students' science process skills.